Paracoccidioides brasiliensis: a mycologic and immunochemical study of a sample isolated from an armadillo (Dasipus novencinctus) - Vidal, Monica Scarpelli Martinelli; Melo, Natalina Takahashi de; Garcia, Nilma Maciel; Del Negro, Gilda Maria Barbaro; Assis, Cezar Mendes de; Heins-Vaccari, Elizabeth Maria; Naiff, Roberto D.; Mendes, Rinaldo Poncio [UNESP]; Lacaz, Carlos da Silva (Instituto de Medicina Tropical, 1995)
Amostra de Paracoccidioides brasiliensis isolada de vísceras (baço e fígado) de um tatu (Dasipus novencinctus) foi estudada do ponto de vista micológico e imunoquímico. O tatu havia sido capturado em área da usina hidroelétrica de Tucuruí (Estado do Pará). Este já havia sido considerado como reservatório enzoótico do Paracoccidioides brasiliensis naquela região. Esta amostra, conservada na Micoteca do Instituto de Medicina Tropical de São Paulo sob o número 135, apresenta todas as características de Paracoccidioides brasiliensis, com elevado poder antigênico e baixa virulência para cobaios e ratos Wistar. A demonstração do exo-antígeno específico do P. brasiliensis, representado pela glicoproteína de peso molecular 43 kDa, foi evidente através das técnicas de Imunodifusão Dupla, Imunoeletroforese, SDS-PAGE e Imunoblotting.

A sample of P. brasiliensis isolated from the spleen and the liver of an armadillo (Dasipus novencinctus) has been analysed under a mycological and immunochemical viewpoint. The armadillo was captured in an area of Tucuruí (State of Pará, Brazil), the animal being already established as an enzootic reservoir of P. brasiliensis at that region of the country. This sample maintained in the fungal collection of the Tropical Medicine Institute of São Paulo (Brazil) numbered 135, has got all the characteristics of P. brasiliensis, with a strong antigenic power and low virulence for guinea-pigs and Wistar rats. The specific exoantigen of P. brasiliensis - the glycoprotein with a molecular weight of 43 kDa - was easily demonstrated with double immunodiffusion, immunoelectrophoresis, SDS-PAGE and immunobloting techniques.
Paracoccidioides brasiliensis: estudo micológico e imunoquímico de amostra isolada de tatu (Dasipus novencinctus)
Keywords: Paracoccidioides brasiliensis; Dasipus novencinctus